A multicentre, prospective, randomized, controlled trial comparing EVARREST™ fibrin sealant patch to standard of care in controlling bleeding following elective hepatectomy: anatomic versus non-anatomic resection. Issue 3 (March 2016) - Koea, Jonathan B.; Batiller, Jonathan; Aguirre, Nicolas; Shen, Jessica; Kocharian, Richard; Bochicchio, Grant; Garden, O. James
Abstract: Background: This multicentre, randomized clinical trial assessed the safety and effectiveness of the EVARREST™ Fibrin Sealant Patch (FP) in treating parenchymal bleeding following anatomic and non-anatomic liver resections. Methods: One hundred and two patients were stratified according to the type of hepatic resection (anatomic/non-anatomic), and randomized (1:1) after identification of an appropriate bleeding site, to FP vs Standard of Care (SoC, manual compression ± topical haemostat). The primary endpoint was haemostasis at 4 min from bleeding site identification with no re-bleeding requiring re-treatment. Results: The FP was superior in achieving haemostasis at 4 min (96%, 48/50) to SoC (46%, 24/52; p < 0.001). Stratification for resection type showed treatment differences for primary endpoint for anatomic (24/25 FP vs 13/23 SoC; p = 0.001) and non-anatomic liver resections (24/25FP vs 11/29 SoC; p < 0.001). Adverse events related to the study procedure were reported in 40/50 patients (80%) in the FP group and 43/52 patients (83%) in the SoC group. One (2%) adverse event (infected intra-abdominal fluid collection) was possibly related to study treatment. Conclusion: This clinical trial confirms that the FP is safe and highly effective in controlling parenchymal bleeding following hepatectomy regardless of the type of resection. ClinicalTrials.govNCT01993888 .